Bad company: Loneliness longitudinally predicts the symptom cluster of pain, fatigue, and depression in older adults. Issue 8 (12th April 2022) - Powell, Victoria D.; Kumar, Navasuja; Galecki, Andrzej T.; Kabeto, Mohammed; Clauw, Daniel J.; Williams, David A.; Hassett, Afton; Silveira, Maria J.
Abstract: Background: Pain, fatigue, and depression frequently co‐occur as a symptom cluster. While commonly occurring in those with cancer and autoimmune disease, the cluster is also found in the absence of systemic illness or inflammation. Loneliness is a common psychosocial stressor associated with the cluster cross‐sectionally. We investigated whether loneliness predicted the development of pain, fatigue, depression, and the symptom cluster over time. Methods: Data from the Health and Retirement Study were used. We included self‐respondents ≥50 year‐old who had at least two measurements of loneliness and the symptom cluster from 2006–2016 ( n  = 5974). Time‐varying loneliness was used to predict pain, fatigue, depression, and the symptom cluster in the subsequent wave(s) using generalized estimating equations (GEE) and adjusting for sociodemographic covariates, living arrangement, and the presence of the symptom(s) at baseline. Results: Loneliness increased the odds of subsequently reporting pain (aOR 1.22, 95% CI 1.08, 1.37), fatigue (aOR 1.47, 95% CI 1.32, 1.65), depression (aOR 2.33, 95% CI 2.02, 2.68), as well as the symptom cluster (aOR 2.15, 95% CI 1.74, 2.67). The median time between the baseline and final follow‐up measurement was 7.6 years (IQR 4.1, 8.2). Conclusions: Loneliness strongly predicts the development of pain, fatigue, and depression as well as the cluster of all three symptoms several years later in a large, nonclinical sample of older American adults. Future studies should examine the multiple pathways through which loneliness may produce this cluster, as well as examine whether other psychosocial stressors also increase risk. It is possible that interventions which address loneliness in older adults may prevent or mitigate the cluster of pain, fatigue, and depression. Abstract : See related article by Kotwal et al . in this issue.